The evacuation of civilians from Burma analysing the 1942 colonial disaster - Leigh, Michael D. (Bloomsbury, 2014)
The string of military defeats during 1942 marked the end of British hegemony in Southeast Asia, finally destroying the myth of British imperial invincibility. The Japanese attack on Burma led to a hurried and often poorly organized evacuation of Indian and European civilians from the country. The evacuation was a public humiliation for the British and marked the end of their role in Burma. The Evacuation of Civilians from Burma investigates the social and political background to the evacuation, and the consequences of its failure
Includes bibliographical references (pages [227]-272) and index
Keywords: Geschichte 1942; World War, 1939-1945 / Burma; World War, 1939-1945 / Evacuation of civilians / Burma; Weltkrieg (1939-1945); Evakuierung; Zweiter Weltkrieg; Inder; Europäer; Birma